Liver Fibrosis Stages Affect Organic Cation Transporter 1/2 Activities in Hepatitis C Virus-Infected Patients - Matheus De Lucca Thomaz; Carolina Pinto Vieira; Juciene Aparecida Caris; Maria Paula Marques; Adriana Rocha; Tiago Antunes Paz; Rosamar Eulira Fontes Rezende; Vera Lucia Lanchote (Pharmaceuticals, 2024)
This study aims to evaluate the impact of liver fibrosis stages of chronic infection with hepatitis C virus (HCV) on the in vivo activity of organic cation transporters (hepatic OCT1 and renal OCT2) using metformin (MET) as a probe drug. Participants allocated in Group 1 (n = 15, mild to moderate liver fibrosis) or 2 (n = 13, advanced liver fibrosis and cirrhosis) received a single MET 50 mg oral dose before direct-acting antiviral (DAA) drug treatment (Phase 1) and 30 days after achieving sustained virologic response (Phase 2). OCT1/2 activity (MET AUC0–24) was found to be reduced by 25% when comparing the two groups in Phase 2 (ratio 0.75 (0.61–0.93), p < 0.05) but not in Phase 1 (ratio 0.81 (0.66–0.98), p > 0.05). When Phases 1 and 2 were compared, no changes were detected in both Groups 1 (ratio 1.10 (0.97–1.24), p > 0.05) and 2 (ratio 1.03 (0.94–1.12), p > 0.05). So, this study shows a reduction of approximately 25% in the in vivo activity of OCT1/2 in participants with advanced liver fibrosis and cirrhosis after achieving sustained virologic response and highlights that OCT1/2 in vivo activity depends on the liver fibrosis stage of chronic HCV infection.